Estimation of velocity change using repeating earthquakes with different locations and focal mechanisms. Issue 6 (14th June 2013) - Kanu, Chinaemerem O.; Snieder, Roel; O'Connell, Dan
Abstract : [1] Codas of repeating earthquakes carry information about the time‐lapse changes in the subsurface or reservoirs. Some of the changes within a reservoir change the seismic velocity, and thereby, the seismic signals that travel through the reservoir. We investigate, both theoretically and numerically, the impact of the perturbations in seismic source properties of used repeating earthquakes on time‐lapse velocity estimation. We derive a criterion for selecting seismic events that can be used in velocity analysis. This criterion depends on the dominant frequency of the signals, the centertime of the used time window in a signal, and the estimated relative velocity change. The criterion provides a consistent framework for monitoring changes in subsurface velocities using microseismic events and the ability to assess the accuracy of the velocity estimations. Key Points: Resolve velocity change with differing sources Use of differing sources needs to be constrained Constraint on the source location difference depends on the signal properties